PEMANFAATAN LINGKUNGAN SEBAGAI MEDIA PEMBELAJARAN OLEH GURU PENJASORKES SEKOLAH MENENGAH PERTAMA DI DAERAH PESISIR KABUPATEN KEBUMEN - Nurzaman, Umar (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2018)
The purpose of this research is to know the types and ways to utilize the environment as a medium of learning by junior high school teachers in the coastal area of Kebumen Regency. This research method using qualitative research approach with data technique using interview technique, observation, and documentation. The subjects of this study consist of 7 junior secondary schools in coastal areas consisting of SMP Negeri 1 Mirit, SMP Negeri 1 Ambal, SMP Negeri 2 Ambal, SMP PGRI 1 Ambal, SMP Negeri 1 Petanahan and SMP Negeri 1 Ayah and SMP Negeri 2 Ayah. The research instrument uses interview guides and photo documentation. The results of environmental research are used as a place of learning in the coastal area Kebumen District, village buildings, beaches, and roads around the school. The environment used as learning media for penjasorkes consists of paper assignment, modification of ball from coconut husk, perforated vessel made from used bucket, paint bucket cover and wood board for supporting learning. The conclusion of this research is the teacher of the coastal area surveyor Kebumen uses various ways to utilize the environment as a place of learning and learning media such as field to learn big ball game and small ball game, while beach and school access road for learning athletics